A study of the inhibitive effect for corrosion of steel in 1.0 M HCl using a new nonionic surfactant based on coumarin moiety: chemical, electrochemical and quantum mechanics calculations. Issue 1 (2nd January 2023) - Bedair, Mahmoud A.; Alosaimi, Eid H.; Melhi, Saad
Abstract: A new nonionic surfactant (NIS), namely, 17-hydroxy-3, 6, 9, 12, 15-pentaoxaheptadecyl-5- ((4-(((17-hydroxy-3, 6, 9, 12, 15-penta oxa hepta decyl) oxy) sulfonyl) phenyl) diazenyl)-2-(2-oxo-2H- chromene-3-carboxamido) benzene sulfonate was synthesized based on condensation reaction between an azo dye and polyethylene glycol. The chemical structure was elucidated from IR and 1H NMR spectral data and surface activity was measured. The inhibitive effect of the resultant NIS toward corrosion of steel in 1.0 M HCl was evaluated by potentiodynamic polarization, impedance spectroscopy (EIS), non-electrochemical methods (weight loss), surface morphology (SEM and EDX) and DFT calculations. The anti-corrosion performance showed an optimal efficiency of 96.04% at the concentration of 7.50 × 10 −4 M from polarization measurements. Both the anodic and cathodic inhibition were acquired from Tafel plots polarizations (TFP). The adsorption of NIS onto steel surface obeyed Langmuir isotherm. In addition, SEM images showed higher surface protection in presence of inhibitor in agreement with a molecular dynamic simulation which exhibited optimal surface alignment between inhibitor and steel. A good agreement between electrochemical methods and DFT calculations was achieved.